Resource control conflict detection mechanism in trustworthy and controllable network - QU Yan-sheng; LUO Jun-zhou; LI Wei; WANG Peng; TAN Jing (Tongxin xuebao)
In order to achieve consistent resource control,a novel conflict detection mechanism was presented in trustworthy and controllable network.It first modeled the resource control system by defining resource state and policy actions,and then detected policies conflicts by simulating policies enforcement.It solves the problem that the traditional conflict detection mechanisms add too much burden to the managers and could only be implemented to certain resource control mechanisms.Experiments verify this mechanism has good performance.